Hypovitaminosis D in Healthy Pregnant Women and their Newborns in Greece - Sideri, Vasiliki; Antonakos, George; Fretzayas, Andreas; Attilakos, Achilleas; Chrelias, Charalambos; Papaevangelou, Vasiliki; Nicolaidou, Polyxeni; Papadopoulou, Anna (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background/Objectives: The aim of this work was to evaluate the current vitamin D status in healthy pregnant women and their newborns living in Greece and assess possible associations between 25(OH)D and anthropometric features of their fetuses and newborns. Materials & Methods: 81 healthy women were monitored during pregnancy. Biochemical markers related to bone metabolism, 25(OH)D and PTH levels were measured in serum samples of mothernewborn pairs at 1st trimester of pregnancy and at delivery in mothers, in cord blood and at the 3rd day of life of newborns. Results: Maternal 25(OH)D levels at the 1st trimester of pregnancy (22.6±9.2ng/ml) were significantly higher than those at delivery (19.2±9.2ng/ml) (p<0.001). Furthermore, umbilical 25(OH)D levels (21.3±9.3ng/ml) were higher than maternal at delivery (p=0.005) and neonatal levels (19.4±10.4 ng/ml) (p=0.021). Only 57.3% of the mothers at the first trimester and 46.7% at delivery as well as 55.8% of the fetuses and 38.5% of the neonates had adequate vitamin D levels (25(OH)D≥30ng/ml). A significant positive correlation was found between fetal femur length at the 22nd week of gestation and maternal 25()D at the 1st trimester of pregnancy (r=0.36, p=0.048) while body length was significantly higher in newborns whose mothers had sufficient 25(OH)D levels (51.5±2.1cm) compared with those whose mothers had insufficient or deficient 25(OH)D levels at delivery (50.6±2.0cm) (p=0.047). Conclusion: The study confirms inadequate levels of vitamin D in pregnant women in Greece associated with inadequate vitamin D levels of their fetuses and newborns.
Keywords: fetus